Nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film as well as preparation method and application thereof
By using nanoparticles/polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film in the antibacterial film, the photocatalytic nanosol is uniformly wrapped around the outside of the polyvinylidene fluoride core layer by coaxial electrospinning technology. The problem of uneven distribution of photocatalytic powders is solved, and efficient photocatalytic and air purification effects are achieved.
Patent Information
- Application Number
- CN202411584258.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, when the photocatalytic powder material is physically mixed with polymer materials and electrospinning, the photocatalytic powder is unevenly distributed in the fiber, resulting in excessive wind resistance of the fiber web or the photocatalytic powder being wrapped in polymer. The fibers cannot be fully exposed and cannot be effectively contacted with pollutants.
The preparation method of nanoparticles/polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film is adopted, and the polyvinylidene fluoride solution is used as the core layer spinning liquid, and the photocatalytic nanosol is used as the cortical spinning liquid, and coaxial electrospinning is used. Wire technology produces nanoparticles/polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial films, controlling the spinning distance, height and angle to ensure that the photocatalytic nanosol is uniformly wrapped outside the polyvinylidene fluoride core layer.
The uniform distribution and effective exposure of photocatalytic nanosols are achieved, which avoids the problem of excessive wind resistance of the fiber web or the enclosure of photocatalytic powders, and improves the photocatalytic performance and air purification effect of the antibacterial film.
Smart Images

Figure CN119433835A_ABST
Abstract
Description
Technical Field
[0002] The invention belongs to the technical field of bioaerosol antibacterial films, and relates to a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film and a preparation method and application thereof. Background Art
[0003] Bioaerosols are small airborne particles with a diameter of 0.001 to 100 μm, which include pathogenic and / or non-pathogenic microorganisms such as viruses, bacteria and fungi. Photocatalysis is a technology that converts solar energy into chemical energy. The reactive oxygen produced by it can kill pathogenic and / or non-pathogenic microorganisms in bioaerosols and has a significant antibacterial effect. Combining photocatalytic technology with air purification equipment can effectively achieve photocatalytic removal of bioaerosols in the environment.
[0004] The Chinese patent application with publication number CN108411406A introduces a method for preparing piezoelectric photocatalytic nanofibers, using piezoelectric photocatalytic composite fibers prepared by coaxial electrospinning, and using the electric field in the interface of the piezoelectric material and the photocatalyst to separate electrons and holes. However, the piezoelectric material used is a piezoelectric ceramic, which needs to be polarized later, is complicated to prepare, is difficult to deform under the action of wind, and is not easy to use in the field of air purification. The Chinese patent application with publication number CN114471712A introduces a method for preparing a piezoelectric photocatalytic film for purifying air, which adds photocatalytic powder, and needs to be mixed with a polymer substrate before electrospinning can be completed. In this method, the powder and the polymer substrate are physically bonded, and the bonding force is weak. In addition, in this method, photocatalytic powder is added to the polymer material for electrospinning. However, in this process, the position of the photocatalytic powder cannot be accurately fixed, and if the particle size is too large, it will block the porosity of the polymer fiber network and cause excessive wind resistance. If the particle size is too small, it is easy to be wrapped inside the polymer fiber and cannot be fully exposed and effectively contact the pollutants. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film and a preparation method and application thereof, thereby solving the technical problems in the prior art of electrostatic spinning after physically mixing the photocatalytic powder material with the polymer material, the uneven distribution of the photocatalytic powder in the fiber, and when the photocatalytic powder is too large, it blocks the fiber pores, causing excessive wind resistance of the fiber network; when the photocatalytic powder is too small, it is easily wrapped in the polymer fiber and cannot be fully exposed, and cannot effectively contact with the pollutants to achieve the purpose of purifying the pollutants.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film, comprising: using a polyvinylidene fluoride solution as a core layer spinning solution, a photocatalytic nanosol as a skin layer spinning solution, and utilizing the polyvinylidene fluoride solution and the photocatalytic nanosol to perform coaxial electrospinning to obtain the nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film; in the coaxial electrospinning process, the spinning distance is 5 to 10 cm, the spinning height is 10 to 20 cm, and the spinning angle is not greater than 90°.
[0008] Preferably, the photocatalytic nano sol is any one of TiO2 sol and ZnO sol.
[0009] Preferably, the pH value of the photocatalytic nanosol is 6-7.
[0010] Preferably, the content of the photocatalytic nanoparticles in the photocatalytic nanosol is 0.01-0.05 g / mL, and the particle size is less than 25 nm.
[0011] Preferably, the polyvinylidene fluoride solution is prepared by adding polyvinylidene fluoride to NN dimethylformamide, heating and stirring at 30 to 70° C. for 10 to 40 minutes; the mass fraction of the polyvinylidene fluoride solution is 5% to 20%.
[0012] Preferably, the volume ratio of the photocatalytic sol to polyvinylidene fluoride is (1-6):1.
[0013] Preferably, during the coaxial electrospinning process, if the volume ratio of the photocatalytic sol to the polyvinylidene fluoride solution is less than 4:1, the photocatalytic sol is loaded once for electrospinning, and the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (0.3-1.9):1; otherwise, the photocatalytic sol is loaded twice for electrospinning, and the volume ratio of the photocatalytic sol loaded twice is 1:1. When the photocatalytic sol is loaded for electrospinning for the first time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (2.2-4):1, and when the photocatalytic sol is loaded for electrospinning for the second time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (2-3.5):1.
[0014] Preferably, in the coaxial electrospinning process, the syringes used have the same specifications.
[0015] A nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film is prepared by the above method;
[0016] The photocatalytic antibacterial film is formed by interweaving photocatalytic nanoparticles / polyvinylidene fluoride composite fibers;
[0017] The photocatalytic nanoparticle / polyvinylidene fluoride composite fiber comprises an inner core layer and an outer skin layer;
[0018] The inner core layer is polyvinylidene fluoride, and the outer skin layer is photocatalytic nanoparticles.
[0019] The above-mentioned nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film is used in air purification equipment.
[0020] Compared with the prior art, the present invention has the following beneficial technical effects:
[0021] The invention discloses a method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film. The method uses a polyvinylidene fluoride solution and a photocatalytic nanosol for coaxial electrostatic spinning to obtain the piezoelectric gain photocatalytic antibacterial film. In the electrostatic spinning process, the spinning distance is 5 to 10 cm, the spinning height is 10 to 20 cm, and the spinning angle is not greater than 90°. By controlling the spinning parameters, the photocatalytic nanosol can be effectively formed into fibers, and the polyvinylidene fluoride solution is used as the core layer spinning solution, and the photocatalytic nanosol is used as the skin layer spinning solution. After spinning, a nanoparticle / polyvinylidene fluoride composite fiber with an inner and outer double-layer structure is obtained. In the composite fiber, the photocatalytic nanosol is the outer skin layer, and the polyvinylidene fluoride is the inner core layer, so that the photocatalytic nanosol is effectively evenly wrapped on the outside of the polyvinylidene fluoride core layer, avoiding the blockage of the fiber pores caused by the nanoparticles during direct mixing for electrostatic spinning, or the nanoparticles are wrapped inside the polymer, affecting its photocatalytic performance. This technology allows photocatalytic sol to be directly applied to the spinning solution. By adjusting the spinning distance, height and angle, it overcomes the problem of insufficient conductivity of inorganic active ingredients and inability to be pulled to the receiver by the electric field. Due to the higher height, downward tilted angle, and closer distance to the receiver, combined with the gravity effect of the droplets themselves, it makes up for the defect of insufficient electric field force and achieves an effect similar to electrostatic spraying. By utilizing the electric field effect of electrospinning and the thermal effect brought by high pressure, polyvinylidene fluoride is pulled to the receiver and compounded with the sol at the critical point of transformation from liquid state to fiber film, avoiding the problem of sol causing polyvinylidene fluoride to precipitate, and the water phase state can be used to make polyvinylidene fluoride undergo phase change, improving its piezoelectric properties. Therefore, the present invention uses electrostatic spinning technology to effectively fix the nanoscale photocatalytic sol on the surface of micron-level polyvinylidene fluoride in one step, ensuring that polyvinylidene fluoride will not coat the effective ingredients, and also ensuring that the effective ingredients will not block the pores of polyvinylidene fluoride fibers, ensuring that polyvinylidene fluoride can build a built-in electric field in the core layer, effectively promoting the effective separation and directional migration of electrons and holes in the surface sol, and making up for the defect that the higher the flow rate, the worse the antibacterial efficiency. High flow provides high stress, promotes polyvinylidene fluoride to build a built-in electric field, and enhances the ability of the sol to remove bioaerosols. The preparation industry is simple, energy consumption is low, and it is easy to scale up production. A preparation method of a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film developed by the present invention does not need to mix the nanoparticles with the polymer, and the nanosol in a liquid state can be directly spun, without the need to configure the spinning solution, and is evenly dispersed and not easy to agglomerate.
[0022] Furthermore, the photocatalytic nanosol is any one of TiO2 sol and ZnO sol, which can have the ability to generate free radicals to kill bacteria under the action of light, and they can be made into nanometer size with a sufficiently small particle size distribution. In addition, after drying, this type of sol directly becomes photocatalytic nanoparticles, without the need for other operations and processing, and is easy to use and easy to apply on a large scale.
[0023] Furthermore, the pH value of the photocatalytic nano-sol is 6-7, which can effectively ensure the stability of the sol and avoid the increase of particle volume caused by its agglomeration and sedimentation, which affects the spinning effect and the catalytic performance of the photocatalytic material.
[0024] Furthermore, the content of photocatalytic nanoparticles in the photocatalytic nanosol is 0.01-0.05 g / mL, which can effectively control the amount of active ingredients and ensure fluidity. In addition, the particle size of the photocatalytic nanoparticles is less than 25 nm. The small particles ensure uniform coverage of the sol on the fiber, and the particle size is small enough not to affect the porosity of the fiber and the wind resistance of the antibacterial film.
[0025] Furthermore, the preparation process of the polyvinylidene fluoride solution is to add polyvinylidene fluoride to NN dimethylformamide, and heat and stir at 30-70°C for 10-40 minutes. This process can ensure that the polyvinylidene fluoride has a high β phase content. The α phase will appear when the temperature is too high or too low, and the higher the β phase, the better the piezoelectric performance.
[0026] Furthermore, the volume ratio of the photocatalytic sol to polyvinylidene fluoride is (1-6):1, which effectively enables the polyvinylidene fluoride fibers to be wrapped and covered by the photocatalytic nanomaterial fibers after spinning.
[0027] Furthermore, during the coaxial electrospinning process, if the volume ratio of the photocatalytic sol to the polyvinylidene fluoride solution is less than 4:1, the photocatalytic sol is loaded once for electrospinning, and the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (0.3-1.9):1; otherwise, the photocatalytic sol is loaded twice for electrospinning, and the volume ratio of the photocatalytic sol loaded twice is 1:1. When the photocatalytic sol is loaded for electrospinning for the first time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (2.2-4):1, and when the photocatalytic sol is loaded for electrospinning for the second time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (2-3.5):1. In this process, when the volume of the photocatalytic sol and the polyvinylidene fluoride solution is relatively small, that is, when the volumes of the two are relatively close, the photocatalytic sol can be loaded once for electrostatic spinning. At this time, the pushing speed of the photocatalytic sol and the polyvinylidene fluoride solution is relatively small, which is (0.3-1.9):1, which can ensure that the core layer and the skin layer maintain similar solid content during spinning, so that the skin layer is evenly loaded. When the volume of the photocatalytic sol and the polyvinylidene fluoride solution is relatively large, the photocatalytic sol needs to be loaded twice for electrostatic spinning, and the pushing speed of the photocatalytic sol and the polyvinylidene fluoride solution is also large. When the photocatalytic sol is loaded twice for spinning, the pushing speed ratios are (2.2-4):1 and (2-3.5):1, respectively, which also ensures that the core layer and the skin layer maintain similar solid content during spinning, so that the skin layer is evenly loaded.
[0028] Furthermore, in the coaxial electrospinning process, the syringes used have the same specifications. If the specifications of the two syringes are too different, it is difficult to control the effective propulsion distance and the spinning distance, height and angle, and it is impossible to obtain good composite spun fibers. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 It is a schematic diagram of the parameter setting structure during electrospinning in the present invention;
[0031] Figure 2 The XRD spectra of the products after preparing polyvinylidene fluoride solutions at different temperatures in the present invention;
[0032] Figure 3 This is an appearance diagram of the product after the polyvinylidene fluoride solution is prepared at different temperatures in the present invention;
[0033] Figure 4 The test results of the antibacterial performance of the nano-photocatalytic antibacterial fibers prepared in Examples 1 to 4 of the present invention against Gram-negative bacteria Escherichia coli;
[0034] Figure 5 This is a SEM image of the piezoelectric photocatalytic film in Example 1 of the present invention;
[0035] Figure 6 TEM image of the piezoelectric photocatalytic film in Example 1 of the present invention;
[0036] Figure 7 This is a SEM image of the piezoelectric photocatalytic film in Example 3 of the present invention;
[0037] Figure 8 is a SEM image of the piezoelectric photocatalytic film in Example 4 of the present invention;
[0038] Fig. 9 It is a schematic cross-sectional view of the photocatalytic nanoparticle / polyvinylidene fluoride composite fiber of the present invention.
[0039] Among them, 1. photocatalytic nanoparticles / polyvinylidene fluoride composite fiber, 11. inner core layer, 12. outer skin layer. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0041] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0042] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0043] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0044] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0045] The invention provides a method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film. The method uses a polyvinylidene fluoride solution as a core layer spinning solution and a photocatalytic nanosol as a skin layer spinning solution, and uses the polyvinylidene fluoride solution and the photocatalytic nanosol to perform coaxial electrostatic spinning to prepare the nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film; in the coaxial electrostatic spinning process, the spinning distance is 5 to 10 cm, the spinning height is 10 to 20 cm, and the spinning angle is not greater than 90°, preferably greater than 0° and not greater than 90°.
[0046] like Figure 1 The figure is a schematic diagram of the parameter setting structure of the electrospinning in the present invention. The spinning distance in the present invention is the horizontal distance between the injection head of the syringe and the axis of the receiver, that is, Figure 1 The L in the figure is the vertical height of the injection head of the syringe from the axis of the receiver, that is, Figure 1 The h in the figure is the angle (acute angle) between the injection head of the syringe and the horizontal direction, that is, Figure 1 When the spinning angle is 0°, the syringe is placed horizontally, and when the spinning angle is 90°, the syringe is placed vertically, that is, the injection head of the syringe is set vertically downward.
[0047] The preparation process of the polyvinylidene fluoride solution is to add polyvinylidene fluoride to NN dimethylformamide, and heat and stir for 10 to 40 minutes at 30 to 70°C; the mass fraction of the polyvinylidene fluoride solution is 5% to 20%. In this process, it can be ensured that the polyvinylidene fluoride has a high β-phase content. The α-phase will appear when the temperature is too high or too low, and the higher the β-phase, the better the piezoelectric performance. The attribution of its crystal phase can be characterized by XRD and Fourier infrared spectroscopy. When the XRD spectrum of polyvinylidene fluoride shows a diffraction peak at 18.6°, it means that α-phase polyvinylidene fluoride is obtained, and a diffraction peak appears at 20.3°, which means that β-phase polyvinylidene fluoride is obtained. In the Fourier infrared spectrum, at 843cm -1 The vibration peak appears, indicating that β-phase polyvinylidene fluoride is obtained, at 764cm -1 The presence of a vibration peak indicates that α-phase polyvinylidene fluoride is obtained, and the content of β-phase can be calculated by formula (1):
[0048]
[0049] In the formula, F β is the content of β phase, A β 843cm in Fourier infrared spectrum -1 The area corresponding to the vibration peak, A α 764cm in the Fourier infrared spectrum -1 The area corresponding to the vibration peak.
[0050] Figure 2 The XRD spectra of the products after preparing polyvinylidene fluoride solution at different temperatures are shown in the figure. It can be seen from the figure that too high or too low temperature will lead to the formation of α-phase polyvinylidene fluoride. Therefore, heating and stirring at 30-70°C can fully obtain β-phase polyvinylidene fluoride and ensure the piezoelectric properties of the product. In addition, Figure 3 As shown, the mass fraction of the polyvinylidene fluoride solution is 5% to 20%. In addition, a uniform and transparent solution can be obtained by heating and stirring at 30 to 70° C., and the stability of the system is better.
[0051] The photocatalytic nanosol is any one of TiO2 sol and ZnO sol. The pH value of the photocatalytic nanosol is 6 to 7. The content of photocatalytic nanoparticles in the photocatalytic nanosol is 0.01 to 0.05 g / mL, and the particle size is less than 25 nm.
[0052] The photocatalytic nanosol described in the present invention is a special nanomaterial. The nanosol is a stable dispersion system formed by nano-scale particles in a liquid medium. These nanoparticles have an extremely small size, usually 1 to 100 nm. Photocatalysis is a process that uses light energy to drive chemical reactions. In the photocatalytic process, the photocatalyst absorbs light energy and converts it into chemical energy, thereby promoting the progress of the chemical reaction.
[0053] The photocatalytic nano-sol described in the present invention is at least one of TiO2 sol and ZnO sol. Among them, TiO2 sol, i.e. titanium dioxide sol, is mainly formed by nano-scale TiO2 particles dispersed in a liquid medium. The preparation method of TiO2 sol in the present invention can refer to the Chinese patent application with publication number CN109734327A. ZnO sol, i.e. zinc oxide sol, is a colloidal system formed by nano-scale ZnO particles dispersed in a liquid medium. The preparation method of ZnO sol in the present invention can refer to the Chinese patent application with publication number CN103236352A.
[0054] In addition, the volume ratio of the photocatalytic sol to polyvinylidene fluoride is (1-6): 1. In the coaxial electrospinning process, the specifications of the syringes used are the same. If the volume ratio of the photocatalytic sol to the polyvinylidene fluoride solution is less than 4:1, the photocatalytic sol is loaded once for electrospinning, and the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (0.3-1.9): 1; otherwise, the photocatalytic sol is loaded twice for electrospinning, and the volume ratio of the photocatalytic sol loaded twice is 1: 1. When the photocatalytic sol is loaded for electrospinning for the first time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (2.2-4): 1, and when the photocatalytic sol is loaded for electrospinning for the second time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (2-3.5): 1.
[0055] In addition, the present invention also discloses a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film prepared by the above method, such as Fig. 9 As shown, the photocatalytic antibacterial film is formed by interweaving photocatalytic nanoparticles / polyvinylidene fluoride composite fibers 1; the photocatalytic nanoparticles / polyvinylidene fluoride composite fibers include an inner core layer 11 and an outer skin layer 12; the inner core layer 11 is polyvinylidene fluoride, and the outer skin layer 12 is photocatalytic nanoparticles.
[0056] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0057] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0058] Example 1
[0059] A method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film, wherein 1 g of polyvinylidene fluoride (PVDF) is added to 7 mL of NN dimethylformamide (DMF), stirred in a water bath at 60°C for 30 min, and a polyvinylidene fluoride solution is obtained, and 5 mL of the polyvinylidene fluoride solution is injected into a 20 mL core layer syringe. 10 mL of TiO2 sol is injected into a 20 mL skin layer syringe. The push rate ratio of the skin layer spinning liquid and the core layer spinning liquid is 1.12, ensuring that the spinning liquid can be spun at the same time. The micro pump is raised to 10 cm, that is, the spinning height is 10 cm, the distance is adjusted to 5 cm, and the angle is adjusted to 40°. The receiving substrate on the receiver is kraft paper, and the obtained spinning fiber is dried at 80°C for 12 hours to obtain a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film.
[0060] Example 2
[0061] A method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film comprises the following steps: adding 1 g of polyvinylidene fluoride to 7 mL of DMF, stirring in a water bath at 60°C for 30 min, and injecting 5 mL into a 20 mL core layer syringe. 15 mL of ZnO sol is injected into a 20 mL skin layer syringe. The pushing rate ratio of the skin layer spinning solution and the core layer spinning solution is 1.92 to ensure that the spinning solutions can be spun at the same time. The micropump is raised to 7 cm, the distance is adjusted to 7 cm, and the angle is adjusted to 45°. The receiving substrate on the receiver is kraft paper. Drying at 80°C for 12 h obtains a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film.
[0062] Example 3
[0063] A method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film comprises the following steps: adding 1 g of polyvinylidene fluoride to 7 mL of DMF, stirring for 30 min in a water bath at 60°C, and injecting 5 mL into a 20 mL core layer syringe. 12.5 mL of TiO2 sol is taken for the first time and injected into a 20 mL skin layer syringe. The pushing rate ratio of the skin layer spinning liquid and the core layer spinning liquid is 2.06. When the polyvinylidene fluoride is half spun and the sol is completely spun, 12.5 mL of sol is taken again. The pushing rate ratio of the skin layer and the core layer spinning liquid is 5.80 for the second time to ensure that the spinning liquid can be spun at the same time. The micro pump is raised to 6 cm, the distance is adjusted to 9 cm, and the angle is adjusted to 55°. The receiving substrate on the receiver is kraft paper. Drying is performed at 80°C for 12 hours to obtain a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film.
[0064] Example 4
[0065] Take 1g of polyvinylidene fluoride and add it to 7mL of DMF. Stir in a water bath at 60℃ for 30min, and take 5mL and inject it into a 20mL core layer syringe. Take 15mL of TiO2 sol for the first time and inject it into a 20mL cortex syringe. The push rate ratio of the cortex spinning liquid and the core spinning liquid is 5.84. When the polyvinylidene fluoride is half spun and the sol is completely spun, take another 15mL of sol. The push rate ratio of the cortex and core spinning liquid for the second time is 16.47 to ensure that the spinning liquid can be spun at the same time. Raise the micro pump to 10cm, adjust the distance to 9cm, and adjust the angle to 35°. The receiving substrate on the receiver is kraft paper. Dry it at 80℃ for 12h to obtain a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film.
[0066] In order to test the antibacterial performance of the nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film in the present invention, the following test process is used: the antibacterial (Escherichia coli) efficiency test is carried out using the material killing biological aerosol efficiency detection device, the filter membrane is washed and the bacterial plate culture is carried out to calculate the antibacterial rate, and the antibacterial rate is: (control group-experimental group) / control group, wherein the bacteria are cultured to a certain concentration of suspension, and then diluted to 108CFU / mL with 0.01M phosphate buffer (PBS, pH value is 7.2-7.4). A medical compressed nebulizer is used to generate a compressed air flow to atomize the bacterial solution at the spray port into droplets with an average size of 1μm. Spray into the chamber of the homemade device, inject gas at a flow rate of 3-5 mL / min, and expose the circular sample (1.5 cm in diameter) directly to the aerosol for 2 hours; immerse the sample completely in PBS buffer, centrifuge at 6000 rpm for 15 minutes, and evenly spread 300 μL of the resulting PBS dilution on the agar plate and incubate at 37°C for 24 hours. The total number of colonies on the agar plate was counted by the standard plate count method, and the antibacterial efficiency was calculated by calculating the ratio of the number of colonies of the sample to be tested to that of the blank sample. The light source used was an ordinary desk lamp. The test results are shown in Tables 1 and Figure 4 As shown in Table 1 and Figure 4 It can be seen that the skin-core structured nano-photocatalytic antibacterial fibers obtained in Examples 1 to 4 exhibited good killing performance against Gram-negative bacteria Escherichia coli, and the removal efficiency reached more than 97% within 2 hours:
[0067] Table 1 Antibacterial efficiency of nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film prepared in Examples 1 to 4
[0068]
[0069] in addition, Figure 5 is a SEM image of the piezoelectric photocatalytic film in Example 1, Figure 6 is a TEM image of the piezoelectric photocatalytic film in Example 1, Figure 5~5It can be seen that the nanosol particles can be uniformly loaded on the surface of PVDF fibers, and the particle size is small enough not to affect the pore size of the fibers.
[0070] Figure 7 This is a SEM image of the piezoelectric photocatalytic film in Example 3. It can be seen from the image that the nanosol particles can be evenly loaded on the surface of the PVDF fiber, and the particle size is small enough not to affect the pore size of the fiber;
[0071] Figure 8 This is a SEM image of the piezoelectric photocatalytic film in Example 4. It can be seen from the image that the nanosol particles can be evenly loaded on the surface of the PVDF fiber, and the particle size is small enough not to affect the pore size of the fiber;
[0072] Example 5
[0073] A method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film comprises the following steps:
[0074] S1: adding polyvinylidene fluoride into NN dimethylformamide, heating and stirring at 30° C. for 40 minutes to obtain the polyvinylidene fluoride solution; the mass fraction of the polyvinylidene fluoride solution is 5%.
[0075] S2: Using polyvinylidene fluoride solution as the core spinning solution and TiO2 sol as the skin spinning solution, the polyvinylidene fluoride solution and the photocatalytic nanosol are used for coaxial electrospinning to obtain the nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film; during the coaxial electrospinning process, the spinning distance is 5 cm, the spinning height is 10 cm, and the spinning angle is 10°. Among them, the pH value of TiO2 sol is 6.5, the content of TiO2 nanoparticles in TiO2 sol is 0.01 g / mL, and the average particle size is 20 nm. During the electrospinning process, the volume ratio of photocatalytic sol to polyvinylidene fluoride is 4:1, and the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is 0.3:1.
[0076] Example 6
[0077] A method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film comprises the following steps:
[0078] S1: adding polyvinylidene fluoride to NN dimethylformamide, heating and stirring at 70° C. for 10 minutes; the mass fraction of the polyvinylidene fluoride solution is 20%.
[0079] S2: Using polyvinylidene fluoride solution as the core spinning solution and TiO2 sol as the skin spinning solution, the polyvinylidene fluoride solution and the photocatalytic nanosol are used for coaxial electrospinning to obtain the nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film; during the coaxial electrospinning process, the spinning distance is 10 cm, the spinning height is 20 cm, and the spinning angle is 85°. Among them, the pH value of TiO2 sol is 7, the content of TiO2 nanoparticles in TiO2 sol is 0.05 g / mL, and the average particle size is 23 nm. During the electrospinning process, the volume ratio of photocatalytic sol to polyvinylidene fluoride is 3:1, and the pushing speed ratio of the photocatalytic sol to polyvinylidene fluoride solution is 1.9:1.
[0080] Example 7
[0081] A method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film comprises the following steps:
[0082] S1: adding polyvinylidene fluoride into NN dimethylformamide, heating and stirring at 50° C. for 30 minutes; the mass fraction of the polyvinylidene fluoride solution is 10%.
[0083] S2: Using polyvinylidene fluoride solution as the core spinning solution and TiO2 sol as the skin spinning solution, the polyvinylidene fluoride solution and the photocatalytic nanosol are used for coaxial electrospinning to obtain the nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film; during the coaxial electrospinning process, the spinning distance is 7 cm, the spinning height is 15 cm, and the spinning angle is 50°. Among them, the pH value of TiO2 sol is 7, the content of TiO2 nanoparticles in TiO2 sol is 0.02 g / mL, and the average particle size is 23 nm. During the electrospinning process, the volume ratio of the photocatalytic sol to polyvinylidene fluoride is 6:1. The photocatalytic sol is loaded twice for electrospinning, and the volume ratio of the photocatalytic sol loaded twice is 1:1. When the photocatalytic sol is loaded for electrospinning for the first time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is 3:1. When the photocatalytic sol is loaded for electrospinning for the second time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is 3.5:1.
[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film, characterized in that: A polyvinylidene fluoride solution is used as a core layer spinning solution, and a photocatalytic nanosol is used as a skin layer spinning solution. The polyvinylidene fluoride solution and the photocatalytic nanosol are used for coaxial electrospinning to obtain the nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film; in the coaxial electrospinning process, the spinning distance is 5 to 10 cm, the spinning height is 10 to 20 cm, and the spinning angle is not greater than 90°.
2. The method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film according to claim 1, characterized in that: The photocatalytic nano sol is any one of TiO2 sol and ZnO sol.
3. The method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film according to claim 1, characterized in that: The pH value of the photocatalytic nanosol is 6-7.
4. The method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film according to claim 1, characterized in that: The content of the photocatalytic nanoparticles in the photocatalytic nanosol is 0.01-0.05 g / mL, and the particle size is less than 25 nm.
5. The method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film according to claim 1, characterized in that: The preparation process of the polyvinylidene fluoride solution is to add polyvinylidene fluoride into NN dimethylformamide, and heat and stir for 10 to 40 minutes at 30 to 70° C. The mass fraction of the polyvinylidene fluoride solution is 5% to 20%.
6. The method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film according to claim 1, characterized in that: The volume ratio of the photocatalytic sol to polyvinylidene fluoride is (1-6):
1.
7. The method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film according to claim 1, characterized in that: During the coaxial electrospinning process, if the volume ratio of the photocatalytic sol to the polyvinylidene fluoride solution is less than 4:1, the photocatalytic sol is loaded once for electrospinning, and the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (0.3-1.9):1; otherwise, the photocatalytic sol is loaded twice for electrospinning, and the volume ratio of the photocatalytic sol loaded twice is 1:
1. When the photocatalytic sol is loaded for electrospinning for the first time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (2.2-4):1, and when the photocatalytic sol is loaded for electrospinning for the second time, the pushing speed ratio of the photocatalytic sol to the polyvinylidene fluoride solution is (2-3.5):
1.
8. The method for preparing a nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film according to claim 1, characterized in that: In the coaxial electrospinning process, the syringes used have the same specifications.
9. A nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film, characterized in that: Prepared by the method according to any one of claims 1 to 8; The photocatalytic antibacterial film is formed by interweaving photocatalytic nanoparticles / polyvinylidene fluoride composite fibers; The photocatalytic nanoparticle / polyvinylidene fluoride composite fiber comprises an inner core layer and an outer skin layer; The inner core layer is polyvinylidene fluoride, and the outer skin layer is photocatalytic nanoparticles.
10. Use of the nanoparticle / polyvinylidene fluoride composite piezoelectric gain photocatalytic antibacterial film described in claim 9 in air purification equipment.
Citation Information
Patent Citations
Preparation method of ZnO sol compounded Sn doping ZnO thick films
CN103236352A
Preparation of titanium dioxide super-hydrophilic self-cleaned photocatalytic film by modified PTA method
CN109734327A
Piezoelectric composite, ink and ink cartridge for 3D printing, bifunctional material comprising the piezoelectric composite, manufacture and uses thereof
CA3043345A1
Preparation method of piezoelectric photocatalysis complex fiber
CN108411406A
Lithium ion battery composite isolation membrane and preparation method thereof
CN108950876A
Cited By
Preparation method and application of efficient antibacterial material based on bionic design
CN120078909A
Piezoelectric-photocatalysis synergistic composite fiber for roads and preparation method of piezoelectric-photocatalysis synergistic composite fiber
CN121593198A
Piezoelectric-optical catalysis synergistic composite fiber for road and preparation method thereof
CN121593198B